High-precision dating and ancient DNA profiling of moa (Aves: Dinornithiformes) eggshell documents a complex feature at Wairau Bar and refines the chronology of New Zealand settlement by Polynesians - Jacomb, C.; Holdaway, R.; Allentoft, M.; Bunce, Michael; Oskam, C.; Walter, R.; Brooks, E. (Academic Press, 2014)
Wairau Bar, New Zealand, is one of the few prehistoric sites in the world that could lay claim to being a site of first human intrusion into a pristine environment. It is certainly one of the best places to study human impact on a hitherto unoccupied land. Its potential status as a colonization phase settlement for New Zealand's Maori population raises questions that require fine-grained chronological resolution. Unfortunately, the simple stratigraphy of the Wairau Bar site has offered little opportunity for the development of high-resolution chronologies. This situation changed recently when new excavations exposed a complex, midden-rich feature which contained a wide range of dateable material, including hundreds of fragments of eggshell of the extinct megaherbivorous moa (Aves: Dinornithiformes). The thick eggshell, with its minimal inbuilt age and high resistance to contamination, is an ideal material for radiocarbon dating. Its refractory properties also allow high-quality preservation of DNA. The moa eggshell yielded radiocarbon that facilitated reconstruction of the chronology of deposition at a fine resolution. Ancient DNA profiling of eggshell fragments was used to ensure that dated fragments were from different individuals. Bayesian analysis of the dated fragments showed that the midden was laid down over a brief period in the early decades of the 14th century CE. This improved chronology provides a benchmark for understanding the duration of site occupation and revises current interpretations of the timing of Polynesian settlement of New Zealand.